In vitro antagonistic activity, plant growth promoting traits and phylogenetic affiliation of rhizobacteria associated with wild plants grown in arid soil - El-Sayed, Wael S.; Akhkha, Abdellah; El-Naggar, Moustafa Y.; Elbadry, Medhat (Frontiers in Microbiology, 2014)
The role of plant growth-promoting rhizobacteria (PGPR) in adaptation of plants in extreme environments is not yet completely understood. For this study native bacteria were isolated from rhizospeheric arid soils and evaluated for both growth-promoting abilities and antagonistic potential against phytopathogenic fungi and nematodes. The phylogentic affiliation of these representative isolates was also characterized. Rhizobacteria associated with eleven wild plant species from the arid soil of Almadinah Almunawarah, Kingdom of Saudi Arabia (KSA) were investigated. From a total of 531 isolates, only 66 bacterial isolates were selected based on their ability to inhibit Fusarium oxysporum, and Sclerotinia sclerotiorum. The selected isolates were screened in vitro for activities related to plant nutrition and plant growth regulation as well as for antifungal and nematicidal traits. Isolated bacteria were found to exhibit capabilities in fix atmospheric nitrogen, produce ammonia, indoleacetic acid (IAA), siderophores, solubilize phosphate and zinc, and showed an antagonistic potential against some phytopathogenic fungi and one nematode species (Meloidogyne incognita) to various extent. Isolates were ranked by their potential ability to function as PGPR. The 66 isolates were genotyped using amplified rDNA restriction analysis (ARDRA) and 16S rRNA gene sequence analysis. The taxonomic composition of the representative genotypes from both rhizosphere and rhizoplane comprised Bacillus, Enterobacter and Pseudomonas. Out of the ten genotypes, three strains designated as PHP03, CCP05, and TAP02 might be regarded as novel strains based on their low similarity percentages and high bootstrap values. The present study clearly identified specific traits in the isolated rhizobacteria, which make them good candidates as PGPR and might contribute to plant adaption to arid environments. Application of such results in agricultural fields may improve and enhance plant growth in arid soils